Enduring Impacts of Aid Quality on Job Choices : The Case of the 2004 Tsunami in Aceh - Nose, Manabu (World Bank, Washington, DC, 2013)
After the tsunami in Aceh, Indonesia, the recovery of fishing was limited while non-fishing sectors temporarily expanded. This paper shows that fishermen's ex-post labor supply responses continued to be constrained by the provision of low quality production assets. The average fishing productivity also declined for the negative selection in response to the aggregate shock. In a natural experiment set-up, it shows widening income inequality after the tsunami for income losses to the recipients of poor quality aid. It suggests the importance of quality monitoring and private market access to sustainably promote rural development after the tsunami.